Inhibitory Test of Endophtic Fungal Metabolites on the Growth of Chilli Seed-Borne Pathogenic Fungi Aspergillus fumigatus - Dewi Novina Sukapiring; Nurbaity Situmorang; Juhardi Sembiring (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
Endophytic fungi are one of the microbes that have been widely used as biological control agents. Endophytic fungi produce metabolites that can inhibit the growth of pathogenic fungi on plants. This study aims to determine the ability of the metabolite compounds produced by endophytic fungi in inhibiting the growth of pathogenic fungi carried by chilli seeds. The method used was the culture of pathogenic fungi, the production of endophytic fungi metabolites using PDYB media and the inhibitory activity of endophytic fungi metabolites on the growth of chilli seed-borne pathogenic fungi Aspergillus fumigatus. The conclusion from the results of the study was that from 2 test isolates the percentage of CECL 38 inhibition against pathogen growth of Aspergillus fumigatus was 50,52% and CECL 19 was 1979%